The histone deacetylase-3 complex contains nuclear receptor corepressors - Wen, Yu-Der (The National Academy of Sciences, 2000)
Acetylation and deacetylation of nucleosomal histones have profound effects on gene transcription in all eukaryotes. In humans, three highly homologous class I and four class II histone deacetylase (HDAC) enzymes have been identified to date. The class I deacetylases HDAC1 and HDAC2 are components of multisubunit complexes, one of which could associate with the nuclear hormone receptor corepressor, N-CoR. N-CoR also interacts with class II deacetylases HDAC4, HDAC5, and HDAC7. In comparison with HDAC1 and HDAC2, HDAC3 remains relatively uncharacterized, and very few proteins have been shown to interact with HDAC3. Using an affinity purification approach, we isolated an enzymatically active HDAC3 complex that contained members of the nuclear receptor corepressor family. Deletion analysis of N-CoR revealed that HDAC3 binds multiple N-CoR regions in vitro and that all of these regions are required for maximal binding in vivo. The N-CoR domains that interact with HDAC3 are distinct from those that bind other HDACs. Transient overexpression of HDAC3 and microinjection of Abs against HDAC3 showed that a component of transcriptional repression mediated by N-CoR depends on HDAC3. Interestingly, data suggest that interaction with a region of N-CoR augments the deacetylase activity of HDAC3. These results provide a possible molecular mechanism for HDAC3 regulation and argue that N-CoR is a platform in which distinct domains can interact with most of the known HDACs.